PERLINDUNGAN KONSUMEN PENGGUNA LISTRIK PASCA BAYAR TERHADAP KENAIKAN TAGIHAN LISTRIK PLN SECARA TIBA-TIBA DIMASA PANDEMI COVID-19 (STUDI KENAIKAN LISTRIK PERIODE APRIL-MEI DAN JUNI 2020) - Jepri Hasiholan; Mariske Myeke Tampi (Fakultas Hukum Universitas Tarumanagara, 2021)
That the recording of the Kwh meter independently that was carried out by PLN during the Covid-19 pandemic in the April, May and June 2020 periods, PLN had violated consumer rights. The articles mentioned are Article 4 letter c and g of the Consumer Protection Law in conjunction with Article 29 Paragraph (1) letter a of the Electricity Law in conjunction with Article 1338 Paragraph (1) KUHPer. PLN does not carry out the obligations that are the rights of consumers and that have become an agreement is a form of violation and injures consumer rights. The existence of Covid-19 cannot be a reason for PLN because it can implement health protocols and in recording meters between consumers and meter registrar employees there is no direct contact. Thus, the Kwh meter recording program independently during the Covid-19 pandemic did not provide protection for consumers. The settlement mechanism that can be carried out is an increase of more than 20 percent, so that the payment for consumers is only required to pay the electricity bill for June 2020 plus 40 percent of the difference between the previous month's bills (March, April and May) using the 3-month average usage rate. Then the remaining 60 percent is paid in the next 3 months at a rate of 20 percent every month.